The effect of diabetes mellitus on the ventricular epicardial activation and repolarization in mice - Vaykshnorayte, M A; Ovechkin, A O; Azarov, J E (Physiological research, 2012)
Cardiac repolarization is prolonged in diabetes mellitus (DM), however the distribution of repolarization durations in diabetic hearts is unknown. We estimated the ventricular repolarization pattern and its relation to the ECG phenomena in diabetic mice. Potential mapping was performed on the anterior ventricular surface in healthy (n=18) and alloxan-induced diabetic (n=12) mice with the 64-electrode array. Activation times, end of repolarization times, and activation-recovery intervals (ARIs) were recorded along with limb lead ECGs. ARIs were shorter in the left as compared to right ventricular leads (P<0.05). The global dispersion of repolarization, interventricular and apicobasal repolarization gradients were greater in DM than in healthy animals (P<0.03). The increased dispersion of repolarization and apicobasal repolarization gradient in DM correlated with the prolonged QTc and Tpeak-Tend intervals, respectively. The increased ventricular repolarization heterogeneity corresponded to the electrocardiographic markers was demonstrated in DM.
Keywords: Animals; experimentální diabetes mellitus; Female; Heart Ventricles; ženské pohlaví; Action Potentials; srdeční komory; Ventricular Function; diabetes mellitus; Mice; Electrocardiography; myši; elektrokardiografie; alloxan; srdce - funkce komor; Alloxan; Male; Diabetes Mellitus; zvířata; mužské pohlaví; akční potenciály; Diabetes Mellitus, Experimental